2013
DOI: 10.1002/rnc.3011
|View full text |Cite
|
Sign up to set email alerts
|

Robust delay-probability-distribution-dependent stability of uncertain stochastic genetic regulatory networks with random discrete delays and distributed delays

Abstract: SUMMARYThis study is concerned with the problem of robust delay‐probability‐distribution‐dependent stability of uncertain stochastic genetic regulatory networks with mixed time‐varying delays. The parameter uncertainties are modeled as having a structured linear fractional form. Besides, we consider that the derivatives of the discrete time delays have different upper bounds in various delay intervals. Moreover, less conservative conditions are obtained by choosing an augmented novel Lyapunov–Krasovskii functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Therefore, it follows from the Lyapunov stability theory that the GRNs (6) with time-varying delays are globally asymptotically stable. Remark 2: It is worth noting that, motivated by [28], the triple integral terms t−σ2 y(s)ds, which is different compared with the results in [29], [30]. Remark 3: Note that the Jensen inequality as in [27] is commonly employed for time-delay systems to deal with the integral terms in the Lyapunov-Krasovskii functional.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, it follows from the Lyapunov stability theory that the GRNs (6) with time-varying delays are globally asymptotically stable. Remark 2: It is worth noting that, motivated by [28], the triple integral terms t−σ2 y(s)ds, which is different compared with the results in [29], [30]. Remark 3: Note that the Jensen inequality as in [27] is commonly employed for time-delay systems to deal with the integral terms in the Lyapunov-Krasovskii functional.…”
Section: Resultsmentioning
confidence: 96%
“…It has been well recognized that time delay is one of the main sources leading to instability and poor performance of a system [7], [8], [9]. As a result, much effort has been paid to the study of GRNs described by FDEMs, and many significant results have been reported in literature on the stability analysis, controller synthesis, filter design, and so on (see, e.g., [7], [8], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28]). …”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of the interaction of gene information in reality, the time delay of the system is not invariable [21][22][23], and it may produce complicated nonlinear phenomena with the change of time. According to literature [24][25][26][27][28], we find that there may be more than one kind of time delay in practical engineering systems.…”
Section: Introductionmentioning
confidence: 99%